Penyuluhan Teknis Tentang Pemanfaatan Air Hujan untuk Penggunaan Rumah Tangga di Dusun Subanglan Desa Binuang Kecamatan Bangkinang - Setiawan, Beny; Islah, Muhammad; Putra, Agus Alisa (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
This Community Service Program aims to provide technical education on the utilization of rainwater as a source of clean water for residents of Subanglan Halet, Binuang Village, Bangkinang District. Despite having high rainfall, the area has not yet optimized rainwater utilization. The approach includes community socialization, the construction of safe rainwater harvesting systems, and training on the use of simple filtration tools to ensure water quality suitable for consumption. The program successfully increased community understanding by 60% regarding rainwater collection and treatment techniques. Community participation reached 80%, demonstrating strong enthusiasm for the program. It is expected the this initiative will benefit the community by improving access to clean water and promoting sustainable environmental management